PENGGUNAAN PERMAINAN BLOOKET DALAM MENINGKATKAN KEAKTIFAN SISWA - Detty Andani; Jasiah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Learning is a teaching and learning interaction that occurs as a result of the mutual influence of teachers and students. In the learning process, the phenomenon of students being less active in studying Islamic Religious Education (PAI) subjects was found. This research aims to show the use of the Blooket game in increasing student activity. The method applied is a qualitative method with observation data collection techniques and the use of the Blooket platform. The results of this research show that the interactive, competitive and fun Blooket platform is considered to encourage students to participate more and take an active role in the learning process.